Loose Part Media Publications Based on Scopus: A Bibliometric Study - Karomah, Rosi Tunas; Ramadhan, Syahrul (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
Loose part media is part of children’s learning. With this media, learning outcomes can be effective. This study aims to present the literature results related to loose part learning media. The data taken came from the help of the r studio program, which is bibliometric r-packages software. The type of data listed is journal articles. In this study related to loose parts, there were increases and decreases in publication numbers, and the highest production peaks in 2018 were 30 articles. The author who produces the most articles about loose parts media for early childhood is Cao, with 14 articles. The country that produces the most articles related to loose parts is the USA, with 332 articles. Most author affiliations are at the Korea Atomic Energy Research Institute, growing from 2007 to 2023, producing 63 articles. The topic trend is that more and more researchers are using loose part materials in various fields, which will make the research carried out more meaningful and more up-to-date.